PENGARUH WEIGHT TRAINING TERHADAP KEMAMPUAN PASSING PADA PESERTA EKSTRAKURIKULER SEPAK BOLA DI SMA NEGERI 9 PONTIANAK - Syarif Muhammad Yunus; Andika Triansyah; Fitriana Puspa Hidasari (Universitas Tanjungpura, 2019)
AbstractThe problem in this study is whether there is an influence of weight training on the passing ability of soccer extracurricular participants in SMA Negeri 9 Pontianak. The purpose of this study was to determine the effect of weight training on passing ability on football extracurricular participants in SMA Negeri 9 Pontianak. The method used in this study is an experimental method with a pre-experimental design research form. The subjects in this study were all participants who joined soccer extracurricular activities in SMA Negeri 9 Pontianak, totaling 20 people. Data analysis with parametric test t-test. The results of the study based on statistical tests note that there is a significant influence on the value of t-test, namely tcount 19.18> ttable 1.729 at a significant level of 5%, from these results it can be concluded that there is an influence of weight training on the passing ability of soccer extracurricular participants in SMA Negeri 9 PontianakKeywords:, Football, Passing, Weight Training